REALIZATION OF IMPLICIT WARNING IN POLITICAL INTERVIEW - Paronyan, Shushanik (Armenian Folia Anglistika, 2022)
The topic of the present article concerns the ways of expressing the speaker’s communicative intent and highlighting the perlocutionary effect of the discursive move in political discourse. The aim of the research is to study the ways of making an impact on the audience in the communicative context of mass media communication. For the purpose of analysis the transcript of a political interview published on the website of the news program Democracy Now is taken. The language material is analysed with the application of contextual-semantic and pragmatic methods of analysis. The study of the dialogic moves of the partners in the question-answer sequences provides ample grounds to suggest that the conversational unit under analysis can be interpreted as a case of macro-warning which creates the perlocutionary effect of alarming. Furthermore, both participants contribute to creating the integrative communicative intent of the interview.